2017
DOI: 10.1094/pdis-08-16-1116-re
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis and QTL Mapping of Resistance to Gummy Stem Blight inCucumis sativusSeedling Stage

Abstract: Gummy stem blight (GSB), caused by Didymella bryoniae (syn. Stagonosporopsis cucurbitacearum), is an important disease of cucumber (Cucumis sativus L.) worldwide. To better understand the resistance to GSB in cucumber seedlings, a set of 160 F9 recombinant inbred lines (RILs) and a total of 405 pairs of SSR primers were employed to detect quantitative trait loci (QTLs) conferring the resistance. Genetic analysis indicated that the resistance to GSB in PI 183967 seedlings was quantitative and mainly governed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 21 publications
2
41
0
Order By: Relevance
“… 53 ) and gsb5.1 (ref. 55 ) seem to be at nearby regions of the two peaks we identified from GWAS in this study on chromosomes 2 and 5, respectively, which obviously need further investigation to confirm. In addition, a recent report also identified a candidate gene for GSB resistance in melon located on chromosome 4 around 4.0 Mb 57 ; however, it does not appear to reside in syntenic regions 58 with the QTL identified this study.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“… 53 ) and gsb5.1 (ref. 55 ) seem to be at nearby regions of the two peaks we identified from GWAS in this study on chromosomes 2 and 5, respectively, which obviously need further investigation to confirm. In addition, a recent report also identified a candidate gene for GSB resistance in melon located on chromosome 4 around 4.0 Mb 57 ; however, it does not appear to reside in syntenic regions 58 with the QTL identified this study.…”
Section: Discussionmentioning
confidence: 70%
“…var. hardwickii ) accession PI 183967 have been reported with some contradictory results 53 , 55 . Liu et al 55 identified six QTL on chromosomes 3, 4, 5, and 6 ( gsb3.1, gsb3.2, gsb3.3, gsb4.1, gsb5.1, and gsb6.1 ) with gsb5.1 as a major QTL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PCR amplification detected no polymorphism to closely related resistance genes (the nearest R genes of GSB-linked SSR marker and eight previously reported GSB R genes) ( Figure S2 ). After aligning the cucumber GSB-linked QTL areas, 114 genes were found in melon chromosome 9, of which only one was an R gene (MELO3C002928) based on its the synteny with the cucumber R gene Csa5G485190 [ 18 ], which is known to be associated with GSB resistance ( Figure 2 and Figure 3 , Table S1 ). Among 35 R genes on melon chromosome 9, 30 were amplified, including the previously reported R gene MELO3C002928 [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comparative genomic analysis revealed that chromosome 5 of cucumber has a syntenic relationship with chromosome 9 of melon [ 16 , 17 ]. A stable quantitative trait locus (QTL; gsb5.1 ) for GSB resistance was also detected on chromosome 5 in cucumber [ 18 ]. Moreover, the second largest cluster of nucleotide-binding site leucine-rich repeat (NBS-LRR) genes has been reported on melon chromosome 9 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%